English English: English - M. Zacky; Nur Futri Ayu Jelita; Nayla Husna Ryanda; Angranini, Angraini (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2024)
Shopee is one of the largest online marketplaces in Indonesia that conducts the buying and selling process through mobile phones and adopts the concept of social media shopping. As the number of Shopee users increases, the challenges and problems increase, as does the quality of service and system accuracy. User interface (UI) plays an important role in shaping user purchase intent. Various previous studies have studied and identified user interface factors that affect Shopee consumer satisfaction, but there is still more information that can be utilized towards comprehensively understanding and analyzing the trends in UI evaluation methods used, as well as trends in UI factors that affect consumer satisfaction, and factors that affect Shopee consumers' purchase intention. Thus, a systematic review of the literature is needed. A total of 120 peer-reviewed research studies were conducted on the research topic of the impact of user interface on shopee application satisfaction published between 2019-2023 and extracted 30 relevant articles from the discussion of inclusion and exclusion criteria. The results of this study found that service quality is the main factor compared to advertisements and free shipping used in evaluating shopee, and user-friendly factors are in the main position that affects the purchase intention of the shopee application. This study provides further research topics that need to be studied further regarding advertising and free shipping in influencing consumer purchase intention seen from the UI on the shopee application.